FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN NELAYAN DI KABUPATEN ACEH SELATAN (STUDI KASUS DI DESA SAWANG BA’U) - Yasrizal Yasrizal (Universitas Teuku Umar, 2016)
Sawang Ba'u is a coastal region village located in South Aceh. There are 1069 fishermen living in this village. This village given major contribution to the production of fish in South Aceh, which amounted to 3,042 tons/year. Capital, work experience, price, and haul as a measure of the high and low fishermen revenue. Therefore, it is necessary to investigate the effect of capital, work experience, price, and haul to fishermen revenue in the Sawang Ba'u South Aceh. Descriptive quantitative approach is used in this study with multiple linear regression model. Sample of this research are 30 fishermen that are taken from total population using incidental sampling method. Sample shown there are 80% samples earn IDR 51,000 up to IDR 70,000 per day. It is also shown 73% of samples have work experience for 11 to 20 years. Everyday 45% of samples would be able to catch 6 kg of fish which reach IDR 25,000 up to IDR 35,000. The result of multiple linear regression shows that capital variable, work experience, price and haul simultaniously have effect on fishermen revenue at Sawang Ba’u village, South Aceh District. In conclusion, capital, sale price and haul of fishes effect the fishermen revenue.